Host innate immune responses of geese infected with goose origin nephrotic astrovirus. (March 2021) - Wang, Zui; Li, Li; Liu, Peng; Wang, Chen; Lu, Qin; Liu, Lina; Yang, Yuying; Luo, Qingping; Shao, Huabin
Abstract: A novel goose astrovirus (GoAstV) outbreak in goslings, characterized by severe articular and visceral gout with high mortality, occurred in China. Although the pathogenesis of GoAstV-infected goslings has been explored in several studies, the host-immune response remains unclear. In this study, a goose astrovirus was isolated from goslings in Xiaogan, and designated as the HBXG strain. The full-length genome of HBXG was 7170 nt. A sequence analysis and phylogenetic trees revealed HBXG belonged to the novel GoAstV. We evaluated the viral distribution systematically and estimated immune related gene expression in HBXG-infected goslings. Results showed that GoAstV replicated quickly in many tissues and the highest titer was observed in the kidney, which reached 10 9.6 copies. TLR3, RIG-I and MDA5 were involved in the host-immune response to GoAstV, and the expression of IFN types I ( IFN-α, IFN-β ), inflammatory cytokines ( IL-8, IL-10, TNF-α ), antiviral proteins (Mx, OASL, PKR) and MHC-I were also upregulated during the infection. In contrast, the expression of proinflammatory cytokines ( IL-1β, IL-6 ) and MHC-II were inhibited at 3 dpi. This study suggests that GoAstV is highly pathogenic to goslings, causing multiple systemic infections in tissues and the host-immune response is activated early in infection. However, rapid viral replication, suppression of inflammatory cytokines (IL-1β, IL-6) and MHC-II expressions were the possible reasons why the host-immune response cannot provide enough protection against GoAstV infection. This study is the first report to illuminate the immune response in goslings infected with GoAstV and offers insight into the pathogenesis of GoAstV. Highlights: A novel goose astrovirus was isolated from goslings in Xiaogan, designated as HBXG strain. We systemically evaluated the viral distribution and immune-related gene expression in HBXG-infected goslings. This study is the first report to illuminate the immune response in goslings infected with GoAstV.